Azithromycin vs. chloramphenicol for uncomplicated typhoid fever in children - Yulia Antolis; Tony Rampengan; Rocky Wilar; Novie Homenta Rampengan (Indonesian Pediatric Society Publishing House, 2013)
Background The emergence of multiple-drug-resistant Salmonella typhi strains has made it necessary to evaluate new agents for the treatment of typhoid fever. Azithromycin has in vitro activity against many enteric pathogens, including Salmonella spp. However, there is not enough evidence to compare azithromycin with first-line antibiotics currently used. Objective To analyze the efficacy of azithromycin compared to that of chloramphenicol as a first-line drug in the therapy of uncomplicated typhoid fever in children. Methods We conducted a randomized open trial from November 2011 to March 2012 on 60 children aged 2-13 years with uncomplicated typhoid fever. Subjects were randomly assigned to receive either azithromycin (10 mg/kgBW /day orally once daily) or chloramphenicol (100 mg/kgBW/day orally in four divided doses) for 7 days. Efficacy was measured by recording clinical cures and fever clearance times. Data was analyzed with Chi-square and T-tests. Results All of 30 patients in the azithromycin group and 28 out of the 30 patients in the chloramphenicol group were cured (P= 0.246). Fever clearance time was shorter in the azithromycin group (mean 37.9 (SD 32.75) hours, 95%CI 25.67 to 50.13) than in the chloramphenicol group (mean 49 (SD 45.83) hours, 95%CI 3 1.89 to 66.11). Conclusions The efficacy of azithromycin is similar to that of choramphenicol in the treatment of uncomplicated typhoid fever in children. Azithromycin has shorter fever clearance time and higher cure rate compared to those of chloramphenicol, although these results are n ot statistically significant.